2023
DOI: 10.3390/biomedicines11020560
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Autofluorescence in Non-Neovascular Age Related Macular Degeneration

Abstract: Quantitative autofluorescence (qAF8) level is a presumed surrogate marker of lipofuscin content in the retina. We investigated the changes in the qAF8 levels in non-neovascular AMD. In this prospective cohort study, Caucasians aged ≥50 years with varying severity of non-neovascular AMD in at least one eye and Snellen visual acuity ≥6/18 were recruited. The qAF8 levels were analysed in the middle eight segments of the Delori pattern (HEYEX software, Heidelberg, Germany). The AMD categories were graded using bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The results showed that qAF8 is decreased during the early progression of AMD. qAF8 levels seem related more to the loss of function and integrity of RPE cells rather than being due to abnormalities in the visual cycle [9].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The results showed that qAF8 is decreased during the early progression of AMD. qAF8 levels seem related more to the loss of function and integrity of RPE cells rather than being due to abnormalities in the visual cycle [9].…”
mentioning
confidence: 95%
“…The quantitative autofluorescence (qAF8) level is a presumed surrogate marker of lipofuscin content in the retina [8]. Chandra et al [9] investigated changes in qAF8 levels in non-neovascular AMD in a prospective cohort study. The AMD categories were graded using both the Beckman classification and multimodal imaging, allowing for the deep phenotyping of AMD.…”
mentioning
confidence: 99%
“… 7 In age-related macular degeneration (AMD), quantitative fluorescence intensity decreases at an early stage of disease and remains reduced into late stage disease. 8 10 …”
mentioning
confidence: 99%